The Effectiveness of Realia in Writing Descriptive Text: a Case of the Seventh Grade Students of SMP N 4 Semarang - Devi Budi Wijaya; Suwandi Suwandi; Sukma Nur Ardini (Universitas PGRI Semarang, 2019)
This study is based on the research which attempted to examine the effectiveness of realia in writing descriptive text by the seventh grade students. The objectives of the research were (1) to analyze and find out the students’ ability in writing descriptive text who are taught by using realia, (2) to analyze and find out the students’ ability in writing descriptive text who are taught without using realia, (3) also to analyze and find out whether there is significant difference between students who are taught by using realia and those taught without using realia. Quasi experimental design was used with the population of 256 seventh grade students of SMP N 4 Semarang in the academic year 2017/2018. By using purposive sampling technique, there were two classes chosen as the sample of this study; vii a and vii b. The instruments of collecting data used were tests; pre-test and post-test. After the data were collected, they were analysed using t-test. The findings were as follows: (1) the ability in writing descriptive text by the students taught using realia was good with the mean of the post-test was 80.21. (2) the ability in writing descriptive text by the students taught without using realia was adequate with the mean of the post-test was 74.44. (3) there was significant difference of the two group students. t-test 4.89 > t-table 2.00. therefore, ha was accepted that realia was effective as a media in teaching writing of descriptive text.